Pemenuhan Hak Anak di Program Paguyuban Anak Ponorogo Perspektif Maqashid Syariah - Nisaul Mustabsiroh; Abid Rohmanu (Journal of Economics, Law, and Humanities, 2024)
The Ponorogo Children's Association (PAP) children's forum realizes its role through various program innovations. Even though it was formed in 2002, it still experiences many obstacles, this can be seen in the many child problems that occur in Ponorogo Regency, such as the issue of high levels of child smoking, high rates of child marriage, child violence, and so on. This shows the importance of maximizing the PAP program as a government partner in supporting the fulfillment of children's rights in Ponorogo Regency. This research is a type of field research using a qualitative approach. Data collection techniques through interviews and documentation related to the Ponorogo Children's Association program. The aim of this research is to analyze the effectiveness of the Paguyuban Anak Ponorogo children's forum program and to determine the elements of protection from a maqashid sharia perspective in efforts to fulfill children's rights in Ponorogo Regency. The results of this research show that the PAP activity program has been running effectively, as proven by Ponorogo Regency receiving the Decent City title for two consecutive years, namely the Pratama title in 2021, Madya in 2022. However, in the process of realizing it, there are still many obstacles. Fulfilling children's rights in accordance with the concept of maqashid sharia, namely civil rights and freedom, rights to a family environment and alternative care, rights to health and welfare, rights to education and use of free time contains elements of maintaining hifzunnafsi, hifzun'aql, and hifzunnasl. The level of urgency is at the tahsiniyah level because the PAP program is only a supporter of other main programs as government partners.